Accountability of Notaries in Issuing Covernotes Related to the Implementation of Credit Agreements at Banks - Budianto, Ari; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to analyze: 1) The form of notary liability for the issuance of notary covernotes used in the process of credit agreements at Bank BPD SULTRA, 2) Legal consequences for the issuance of notary covernotes used in implementing credit agreements at Bank BPD Sultra. The use of research methods is qualitative research through a sociological juridical approach and research specifications in the form of descriptive analysis. The type of data used is primary data derived from interviews and documentation, secondary data through library research, the data analysis method used is descriptive qualitative data analysis. The results of this study conclude that: 1) Notaries must keep their promises based on the cover notes issued, the emergence of problems in the covernote causes the notary to be held accountable by resolving the problem, even though there are no administrative sanctions in accordance with UUJN because covernotes are not regulated in the law, the notary still has a social burden to bear because he is considered negligent in his obligations and the loss of public trust in the notary said, as a form of responsibility the notary will issue an extension cover note to ask for an extension of time in resolving the problem. 2) The legal consequences arising from unresolved covernotes and causing losses to related parties will rely on several points, namely: a notary may be subject to professional responsibility, including the obligation to compensate for losses incurred, A notary may be subject to disciplinary action by the supervisory body or authorized notary institution in the form of a warning, reprimand, or revocation of a notary's license to practice lawsuits which may include demands for compensation, cancellation of transactions, or other legal actions deemed appropriate for the losses suffered.